Phenomenology as Proto-Computationalism: Do the Prolegomena Indicate a Computational Reading of the Logical Investigations? - Lopes, Jesse D. (Husserl Studies, 2023)
This is very important for our argument, since Husserl has previously in the I Prolegomena i identified a mechanism (the thought-machine) that might explain the descriptions (in ideal evaluation) that follow the I Prolegomena i . The causal connection between the mechanics and the computation in fact is Husserl's point of view - indeed Adorno is explicating Husserl. But just as in the earlier essay, Husserl does not think a I biological i interpretation of the thought-economy is adequate to "the most important fact we know about minds" - namely, that mental processes preserve truth (Fodor [15], 9)[9]. McIntyre believes the central difference between Husserl and Fodor is that Husserl does not want to reduce intentionality to syntax, whereas Fodor does. Husserl's Denkmaschine Perhaps the most important source of evidence for the determination of our question can be found in that semi-famous passage of the I Prolegomena i (1900) where Husserl reveals a commitment to the computational nature of thought processes ([27], 79/2001, 50).